การใช้ที่ดินภาคเกษตรกรรมและภาคอุตสาหกรรมในพื้นที่อำเภอสามพราน จังหวัดนครปฐม - ชิดชนก สงวนทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Sampran district of Nakhonpathom province is located next to Bangkok. It is the center of the biggest developed town in Thailand and is next to Om noi industrial estate in Samutsakhon province, the big industrial zone. This makes to gain advantages in location and convenient transportation. That means now Sampran district has many factories. There are about 1,053 factories and 66,852 labours. The industrials make much income for Nakhonpathom province. Sampran district is rich of water sources and good quality of soil that make Sampran district famous in growing fruits such as a pomelos, grapes, guavas and orchids. Sampran district is the main area to produce agricultural products that is important for Bangkok province and vicinities. From this situation, we can see that agricultural is the basal majority of mechanical production in Sampran district and at the same time industrial is the main mechanical for develop the economic growth of Sampran district. But industrial are more expand that make to land use in industrial to expand in scatter and to move forward to fertile agriculture areas. Those areas are destroyed and lastly disappeared. From the case study found that Doth of agricultural and industrial in Sampran district have the important and potentiality in extremely development. Therefore, to determine the goal of Sampran district development is "keeping areas of agricultural and industrial to coexist" by offering method of developing in agricultural and industrial that plan to land use by zoning agricultural and industrial areas. And plans for supporting agricultural and industrial that is plan for supporting agroindustry, plan for supporting agricultural and industrial. Each plan offers a measurement for conduct too.